Asymmetric Trajectories in the Automotive Green Transition: A Hybrid FMEA–AHP Risk Assessment of Developed Versus Emerging Market Resilience - Alexandru-Silviu Goga; Mircea Boșcoianu; Giraudo Maxime (MDPI, 2026)
Abstract This paper proposes and validates a hybrid FMEA-AHP framework designed to quantify the systemic asymmetries inherent in the automotive green transition. By moving beyond traditional component-level failure analysis, this model introduces the Market Maturity Coefficient (km), a novel diagnostic tool that benchmarks transition readiness by comparing risk profiles across divergent geoeconomic landscapes. Utilizing France and Romania as proxies for developed and emerging markets, the research demonstrates a significant “RPN Divergence,” where infrastructure and grid risks in emerging contexts are effectively amplified by factors exceeding 8.0× compared to developed counterparts. The results indicate that while software and technological risks show convergence (km ≈ 1.3), systemic vulnerabilities regarding grid stability and digital maturity remain the primary barriers to a uniform European transition. This framework provides policymakers with a mathematically rigorous met